THE INFLUENCE OF RELAXATION TECHNIQUES ON UTERINE INVOLUTION IN NORMAL POST PARTUM MOTHERS - Saadah Handayani (The Shine Cahaya Dunia Kebidanan, 2022)
Background : One of the causes of bleeding is failure in uterine involution called subinvolution. Subinvolution of the uterus that is not treated properly, will result in continued bleeding or postpartum haemorrhage. Relaxation techniques help mothers feel comfortable and relaxed so that they get peace of mind and have positive suggestions that have an impact on the postpartum period on the process of uterine involution. Objective: To determine the effect of relaxation techniques on uterine involution in normal postpartum. Methods: This research is a Quasy experiment research with a research design of One group pretest posttest design. The population of postpartum in Juli 2022 at the Kabunan Public Health Center, Pemalang Regency with a total of 107 with purposive sampling technique totaling 16 samples of postpartum. Result : There is an effect of relaxation technique on uterine involution in normal postpartum. Analysis of the data using the Wilcoxon test with a value of 0.039 or asym.sig <0.05.